2003
DOI: 10.1093/brain/awg244
|View full text |Cite
|
Sign up to set email alerts
|

Dominant and recessive central core disease associated with RYR1 mutations and fetal akinesia

Abstract: We studied seven patients (fetuses/infants) from six unrelated families affected by central core disease (CCD) and presenting with a fetal akinesia syndrome. Two fetuses died before birth (at 31 and 32 weeks) and five infants presented severe symptoms at birth (multiple arthrogryposis, congenital dislocation of the hips, severe hypotonia and hypotrophy, skeletal and feet deformities, kyphoscoliosis, etc.). Histochemical and ultrastructural studies of muscle biopsies confirmed the diagnosis of CCD showing uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 24 publications
3
120
0
Order By: Relevance
“…Findings such as decreased fetal movement, polyhydramnios, hypotonia, arthrogryposis, respiratory insufficiency, and feeding difficulties were seen in nearly all patients in this series, and are consistent with previously reported cases of the severe neonatal phenotype. 9,16 Patient 10 with a de novo dominant mutation had clinically impressive spinal rigidity of neonatal onset. In addition, early-onset kyphoscoliosis as well as a rapid and early progression of scoliosis was seen in 4 patients, 1 of whom demonstrated paraspinal muscle involvement on muscle ultrasound.…”
Section: Pathologymentioning
confidence: 99%
“…Findings such as decreased fetal movement, polyhydramnios, hypotonia, arthrogryposis, respiratory insufficiency, and feeding difficulties were seen in nearly all patients in this series, and are consistent with previously reported cases of the severe neonatal phenotype. 9,16 Patient 10 with a de novo dominant mutation had clinically impressive spinal rigidity of neonatal onset. In addition, early-onset kyphoscoliosis as well as a rapid and early progression of scoliosis was seen in 4 patients, 1 of whom demonstrated paraspinal muscle involvement on muscle ultrasound.…”
Section: Pathologymentioning
confidence: 99%
“…1). The two mutations were linked to CCD in several unrelated families (3,16,30). Homozygous expression of CCD mutations RyR1-G4898E and ϪG4898R in myotubes lacking RyR1 resulted in minimal caffeine-induced Ca 2ϩ release, which suggested that the two mutants did not release significant amounts of Ca 2ϩ from SR (31).…”
Section: Discussionmentioning
confidence: 99%
“…Arthrogryposis also occurs in infants with inherited mutations in genes that encode skeletal muscle acetylcholine receptor proteins, or proteins associated with these receptors (e.g., rapsyn [RAPSN]) [53][54][55] . Congenital myopathies that are sometimes associated with arthrogryposis can be caused by mutations of genes that encode fetal skeletal-muscle myosin heavy chains 32,56 , skeletal-muscle thin filament proteins 57,58 , and the ryanodine receptor protein [59][60][61] . Congenital myotonic dystrophy causes arthrogryposis 62 because of the toxicity of RNA encoded by a triplet repeat expansion in the 3-prime untranslated region of the dystrophia myotonica protein kinase (DMPK) gene 63 .…”
Section: Neuromuscular Causes Of Arthrogryposismentioning
confidence: 99%